Intergenerational Value Differences in Contemporary Lithuanian Society - Žiliukaitė, Rūta (Sociologija. Mintis ir veiksmas, 2017)
The article uses European Value Survey data to analyze intergenerational differences in Lithuanian society in the domains of religion, morality, family, work and sociopolitical attitudes and the development of these differences during the twenty years of independence. Results of the analysis show a trend of an intercohort value change in 1990-2008 toward increasing individual secularization, moderation of conservative attitudes in the domains of family and individual sexual morality as well as leniency toward breaches of public morality. The development of work-related attitudes does not show any intercohort differences in value orientations. These trajectories of development can be explained by a variety of interrelated macro-level factors: Lithuanian cultural and historical heritage, structural changes that took place in the transition of society, characteristics of the existing institutional context, modernization of society, media- and globalization-induced spread of Western culture.